PENGARUH PEMBELAJARAN KIMIA BERBASIS MASALAH BERVISI SETS TERHADAP KETERAMPILAN GENERIK SAINS - Samiana, Kiki; Binadja, Achmad; Saptorini, Saptorini (Chemistry in Education, 2013)
The aims of research to determine the influence of problem-based learning chemistry SETS vision to generic science skills SMA in the achievement of competencies related hydrocarbon. The research design used a pretest-posttest control group. Method which is used to collect data is documentation, test, observation and questionnaire. Based on test results obtained Normalized Gain generic science skills of experiment group the symbolic language 0,59, the law of cause and effect 0,59, and 0,80 abstraction. While n-gain generic science skills of control group the symbolic language 0,28, the law of cause and effect 0,50, and abstraction 0,76. The average value of post-test experimental group 68 and the control group 45. The average value of affective experimental group 94 and the control group 90. The average value of psychomotor experimental group 86 and the control group 80. The test results obtained correlation biserial (rb) 0,69 with a coefficient of determination (KD) 48%. It can be concluded that the influence of problem-based learning chemistry SETS vision to generic science skills SMA in the achievement of competencies related to hydrocarbon by 48%.